The women's issue: far beyond the law (Revista do Tribunal Regional Federal da 3ª Região, 2019)
This article aims to address the issue of women and their relationship with the law, beyond the paradigms traditionally based on this topic. Our foundation lies in the theoretical propositions of the Russian jurist Evguiéni Pachukanis and the French philosopher Louis Althusser. The Russian jurist, based on Marx's mature works, points out that Law is a structuring and necessary form of capitalism, given that, in this mode of production, it is essential that people take on the social form of legal subjectivity, which does not derive from the norm, but from the materiality of social relations. Likewise, the state political form - derived directly from the mercantile form, just like the legal form - has a structural character in capitalist society. Althusser, in turn, developed an in-depth study of ideology, demonstrating that ideological patterns operate in the unconscious, constituting subjectivities based on concrete material practices. For the French philosopher, legal ideology plays a fundamental role in capitalism, guaranteeing its reproduction. Machismo belongs to the ideological framework of capitalism, because this mode of production is not only structured on the exploitation of labor, but also on multiple oppressions.• Considering the intrinsic imbrication between law, the state and capitalism, it is clear that the root of exploitation and oppression will not be extirpated through law. Although legal measures may be important in terms of alleviating the oppression suffered by women, the end of patriarchy will not come about through the law.
Keywords: woman; feminism; capitalism; Law; State; Althusser; Pachukanis